Exposure Assessment Tools for Hypersensitivity Pneumonitis. An Official American Thoracic Society Workshop Report - Johannson, Kerri A. (Ann Am Thorac Soc, 2020)
This report is based on proceedings from the Exposure Assessment Tools for Hypersensitivity Pneumonitis (HP) Workshop, sponsored by the American Thoracic Society, that took place on May 18, 2019, in Dallas, Texas. The workshop was initiated by members from the Environmental, Occupational, and Population Health and Clinical Problems Assemblies of the American Thoracic Society. Participants included international experts from pulmonary medicine, occupational medicine, radiology, pathology, and exposure science. The meeting objectives were to 1) define currently available tools for exposure assessment in evaluation of HP, 2) describe the evidence base supporting the role for these exposure assessment tools in HP evaluation, 3) identify limitations and barriers to each tool’s implementation in clinical practice, 4) determine which exposure assessment tools demonstrate the best performance characteristics and applicability, and 5) identify research needs for improving exposure assessment tools for HP. Specific discussion topics included history-taking and exposure questionnaires, antigen avoidance, environmental assessment, specific inhalational challenge, serum-specific IgG testing, skin testing, lymphocyte proliferation testing, and a multidisciplinary team approach. Priorities for research in this area were identified.